The Effect of Valerian Root Extract on Reducing Dysmenorrhea Pain Levels and Endorphin Hormone Levels in Women of Childbearing Age - Shinny Ria Pratiwi (Archives of The Medicine and Case Reports, 2023)
Dysmenorrhea is pain in the stomach that interferes with activities. The incidence of dysmenorrhea is 64.25% of the total number of fertile women. Dysmenorrhea causes complaints of weakness, to anxiety due to severe cramps. Dysmenorrhea treatment can be carried out non-pharmacologically with valerian root extract which can have a relaxing effect on the central nervous system, reduce stress and anxiety, and improve sleep quality. This study aimed to analyze the effect of valerian root extract on dysmenorrhea pain levels and endorphins levels in women of childbearing age. This study used an experimental design with a pretest posttest randomized control group design. Sampling using simple sampling technique was divided into 2 groups to measure the intensity of menstrual pain. The intervention group 18 people were given valerian root extract and the control group 18 people were given standard drugs for the treatment of dysmenorrhea. Giving valerian root extract 100 mg was effective in reducing the level of dysmenorrhea pain, p<0.05. Endorphin levels in the intervention group differed from the control group by, p <0.05. Giving valerian root extract is effective in reducing dysmenorrhea pain and increasing endorphins in women of childbearing age.